The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1016/s0925-4773(01)00555-x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific expression of the Ets gene Xsap-1 during Xenopus laevis development

Abstract: We report the cloning of Xenopus laevis Xsap-1 cDNA, encoding a member of the ternary complex factor subfamily of ETS transcription factors. The expression pattern of Xsap-1 was examined during Xenopus embryogenesis using whole-mount in situ hybridization. Spatial expression of Xsap-1 mRNA is first detected at the animal pole at the mid-blastula stage. During neurulation Xsap-1 is expressed in cells participating in neural tube formation, in the sensorial layer of the epidermal ectoderm, and in an anterior reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Several regulatory serum response elements (SREs) are clustered near its core promoter region (16,17) that are bound cooperatively by the MADS box protein serum response factor (SRF) and one member of the ternary complex factor (TCF) family that includes ELK1, SAP1 (SRF accessory protein-1), and NET [new ets (E twenty-six) factor] (18). Orthologous TCF factors are expressed in humans and mice, and similar factors have been identified in Xenopus and zebrafish (19)(20)(21). These TCFs constitute a subfamily of the larger ets superfamily of DNA binding transcription factors (22).…”
Section: Introductionmentioning
confidence: 99%
“…Several regulatory serum response elements (SREs) are clustered near its core promoter region (16,17) that are bound cooperatively by the MADS box protein serum response factor (SRF) and one member of the ternary complex factor (TCF) family that includes ELK1, SAP1 (SRF accessory protein-1), and NET [new ets (E twenty-six) factor] (18). Orthologous TCF factors are expressed in humans and mice, and similar factors have been identified in Xenopus and zebrafish (19)(20)(21). These TCFs constitute a subfamily of the larger ets superfamily of DNA binding transcription factors (22).…”
Section: Introductionmentioning
confidence: 99%
“…A second human elk-1 chromosomal location was first described as the elk-2 locus (Rao et al, 1989), but has finally been shown to correspond to two elk-1-related processed pseudogenes embedded in the IgH locus (Harindranath et al, 1998). TCF like factors have been identified in Xenopus, (Nentwich et al, 2001), Goldfish (Goldman et al, 1998), Zebrafish (Brown et al, 1999) and Caenorhabditis elegans (Beitel et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In Xenopus, zebrafish and chick, Ets expression is initiated in premigratory crest, while Twist comes on in early migrating crest [33,[38][39][40][41]. In lamprey, four homologues of Twist and three of Ets have been identified; all of these genes are expressed in postmigratory crest cells [32].…”
Section: The Nc-grn In the Lampreymentioning
confidence: 99%